Effect of commercial dental investments at low temperature on the marginal adaptation of cast cp Ti inlays - Rodrigo Galo; Ricardo Faria Ribeiro; Maria da Glória Chiarello de Mattos; Fernanda de Carvalho Panzeri Pires de Souza (Universidade Estadual de Campinas, 2015)
Aim: The purpose of this study was to evaluate the adaptation of inlay restorations cast in commercially pure titanium (cp Ti) after inclusion of the wax patterns in either a phosphate-bonded investment (Rematitan Plus® ) or a silicon oxide-based investment (Termocast® ). Methods: The wax patterns were prepared over an inlay-type mold. After waxing, 5 measurements of the marginal adaptation were made on the mesial and distal faces. Five wax patterns were included in each type of investment under vacuum. The cast specimens were repositioned in the mold and other 5 measurements of the adaptation were made based on the same initial testing conditions. Data were analyzed statistically by two-way ANOVA and Duncan's post-hoc (P<0.01) using the SPSS statistical software package version 12.0 (SPSS, Chicago, IL, USA). Results: The mean marginal discrepancies of the MOD inlays were higher in the Termocast® Group. Termocast® presented significantly greater marginal discrepancy than Rematitan Plus® . Due to the great permeability of the investment refractory material, internal porosity was extremely rare in Rematitan Plus® and more common in Termocast® . Conclusion: It may be concluded that Termocast® investment should not be indicated for cp Ti casting due to poor adaptation and porosity on the casting surface.